Prevalence of anemia in pregnant mothers and their outcome: a study in a semi urban area - Srilatha, Juvvadi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: One of the most common disorders associated with nutritional deficiencies is anaemia. The etiology of anemia during pregnancy among women in developing countries is multifactorial and varies by geographic region. Hence this study was conducted to assess the prevalence of anemia among the pregnant women in our geographical area along with the outcome. Methods: The patients age, weight, BMI, parity, etc were noted and blood was collected for blood investigations which included random sugar levels, complete blood picture apart feom haemoglobin levels. Hemoglobin was calculated by Sahli’s method and classified according to the WHO classification for pregnant women. Results: The predominant age group of the 486 patients was 20-24 years, followed by 25-29 years. 291 out of the 486 patients (59.9%) were anemic and 40.1% of the patients were non anemic. 19.8% of the patients had mild anemia, 33.3% of the patients had moderate anemia, and 6.8% of the patients had severe anemia. Conclusions: Information and interaction, and good nutritional diet and medication is important to reduce the incidences of anemia and thereby the morbidity and mortality associated with it.